Ncx3 gene ablation impairs oligodendrocyte precursor response and increases susceptibility to experimental autoimmune encephalomyelitis. Issue 7 (27th April 2016) - Casamassa, Antonella; La Rocca, Claudia; Sokolow, Sophie; Herchuelz, Andre; Matarese, Giuseppe; Annunziato, Lucio; Boscia, Francesca
Abstract : The Na + /Ca 2+ exchanger NCX3, recently identified as a myelin membrane component, is involved in the regulation of [Ca 2+ ]i during oligodendrocyte maturation. Here NCX3 involvement was studied in myelin oligodendrocyte glycoprotein (MOG)‐induced experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. Western blotting and quantitative colocalization studies performed in wild‐type ncx3 +/+ mice at different stages of EAE disease showed that NCX3 protein was intensely upregulated during the chronic stage, where it was intensely coexpressed with the oligodendrocyte precursor cells (OPC) marker NG2 and the premyelinating marker CNPase. Moreover, MOG35‐55 ‐immunized mice lacking the ncx3 gene displayed not only a reduced diameter of axons and an intact myelin ring number but also a dramatic decrease in OPC and pre‐myelinating cells in the white matter of the spinal cord when compared with ncx3 +/+ . Accordingly, ncx3 −/− and ncx3 +/− mutants developed early onset of EAE and more severe clinical symptoms. Interestingly, cytofluorimetric analysis revealed that during the peak stage of the disease, the number of immune T‐cell subsets in ncx3 −/− mice, was not statistically different from that measured in ncx3 +/+ . Our findings demonstrate that knocking‐out NCX3 impairs oligodendrocyte response and worsens clinical symptoms in EAE without altering the immune T‐cell population. GLIA 2016;64:1124–1137 Main Points: Our findings demonstrate that knocking‐out NCX3 impairs oligodendrocyte response and worsens clinical symptoms in EAE without altering the immune T‐cell population. NCX3 is coexpressed and upregulated in oligodendrocyte lineage cells during EAE. Ncx3 −/− mice exhibited increased severity of EAE, unaltered immune responses in the peak stage, and impaired oligodendrocyte lineage responses in the chronic stage.